Decision theory with a state of mind represented by an element of a Hilbert space: The Ellsberg paradox - Eichberger, Jürgen; Pirner, Hans J. (Journal of mathematical economics, 2018)
In this paper, we propose an interpretation of the Hilbert space method used in quantum theory in the context of decision making under uncertainty. For a clear comparison we will stay as close as possible to the framework of SEU suggested by Savage (1954). We will use the Ellsberg (1961) paradox to illustrate the potential of our approach to deal with well-known paradoxes of decision theory.